Prevalence and relationship between metabolic syndrome and risk of cardiovascular disease: Evidence from two population-based studies. (December 2020) - Alieva, Asiiat S.; Olmastroni, Elena; Reutova, Olga V.; Rotar, Oxana P.; Konradi, Alexandra O.; Shlyakhto, Evgeny V.; Baragetti, Andrea; Grigore, Liliana; Pellegatta, Fabio; Casula, Manuela; Tragni, Elena; Catapano, Alberico L.
Abstract: Background and aim: The metabolic syndrome (MetS) has become one of the most important clinical issues in the cardiovascular field for this decade because of the marked increase in cardiovascular (CV) risk associated with a clustering of risk factors. The aim of the current study was to evaluate the relationship between MetS and its components and cardiovascular disease (CVD). Methods: This population-based cross-sectional study was based on data from two studies carried out in Russia (ESSE-RF) and Italy (PLIC). One sample from each cohort was selected, matching individuals by sex and age. A comparison between samples of MetS components distribution and CV risk, according to SCORE chart, has been conducted. Results: A total of 609 individuals (mean [SD] age 55 [8] years, about 39% males) for each cohort were selected. Almost half of PLIC cohort participants belonged to the moderate CV risk group (47% vs 27%), while in ESSE-RF cohort a relatively higher prevalence of individuals classified in the high and very high risk group was observed (19% vs 11%, 21% vs 6%, respectively). Overall, 43% of ESSE-RF participants were diagnosed with MetS, compared with the 27% of PLIC members (the difference in prevalence becomes 37% vs 21%, considering a more conservative cut-off for waist circumference). Both cohorts showed a trend towards the increase of MetS components moving from the lowest to the highest CV risk class, with a high prevalence of patients with four or five MetS determinants allocated in the high/very high CV risk group. Conclusions: Developing effective public health strategies for the prevention, detection and treatment of MetS should be an urgent priority to reduce the burden of CVD, not only in subjects at high/very high CV risk, but also in those characterized by a lower risk, as even rare CV events that come from low risk group bring a tangible burden to healthcare systems. Graphical abstract: Image 1 Highlights: MetS has become one of the most important clinical issues in the CV field. A cross-sectional study was carried out in Russia (ESSE-RF) and Italy (PLIC). Both cohorts showed a trend towards the increase of MetS components. Developing health strategies to prevent and treat MetS will reduce the CVD burden.